(untitled) (AYUSHDHARA, 2018)
Ayurveda is the oldest of all remedial sciences in the world. Eranda (Ricinus Communis Linn.) commonly known as Castor plant is widespread throughout Tropical region. It is one of the important Ayurvedic herb used for centuries and oil has wide range of therapeutic properties. Castor oil has a multitude of uses in both the health and industrial sectors. Eranda thaila is one of the main drugs used for Virechana karma (purgative therapy) and Snehana karma (Oleation therapy) under Panchakarama therapy. It pacifies Vata, the aggravation of which is the root cause of all diseases. Among Chatusnehas (four types of unctuous materials), Thaila (oil) is the best for the management of Vatavyadhi (diseases of Vata) as it possess opposite Gunas (properties) of Vata. In Vatika vikaras (disorders caused by Vata) Sneha virechana (purgation by oil) is advised, as it clears obstruction in the Srotas (body channels) and relieves Vata vitiation subsequently. Eranda thaila (Castor oil) is one of widely used oil in Ayurvedic disease management both internally and externally. In Samhitas it is mentioned to be Vata Kaphahara and Adhobhaga doshahara (disorders of lower parts of the body) and has been praised for its Amvathahara (rheumatoid arthritis) property. It is also administered as adjuvant for various formulations. Eranda thaila (Castor oil) is a wonderful drug which can also rejuvenate the body and can be administered in many ways. Even though it has various medicinal properties, inappropriate usage causes adverse effects such as dizziness, abdominal cramps, diarrhoea; etc. Castor oil mainly consists of Ricinoleic acid.